Relationship between serum insulin and point-of-admission blood glucose of ill neonates at a tertiary health facility in Nigeria - Adeniji, Emmanuel Oluwatosin (Pan Afr Med J, 2020)
INTRODUCTION: Optimal glucose metabolism is important in neonatal survival especially in the first days of life. Insulin play a significant role in maintaining blood glucose homeostasis. This study set out to determine the serum insulin levels of ill neonates as related to their point-of-admission blood glucose estimation at the Wesley Guild Hospital, Ilesa, Nigeria. METHODS: Three hundred babies took part in the study. Blood glucose and serum insulin levels were assayed at admission using Accu-Chek Active glucometer((R)) and Accu-Ɔ-Bind ELISA Microwells((R)) respectively. Hyperglycaemia was defined as blood glucose ≥7mmol/L and hypoglycaemia as blood glucose <2.2mmol/L. RESULTS: The median (IQR) age of the babies was 10.0 (0.5 - 70.0) hours with male to female ratio of 1.5:1. Seventy-four (24.7%) were preterms and 35 (11.7%) were small-for-gestational age. The mean (SD) blood glucose level of the babies was 4.1(2.1) mmol/L with a range of 0.6-13.4mmol/L. Hyperglycaemia and hypoglycaemia were observed in 18(6.0%) and 40(13.3%) babies respectively. The median (IQR) serum insulin level was 9.8(3.0-35.3) μIU/ml. There was weak positive correlation between serum insulin and blood glucose levels of the babies (r = 0.197, p = 0.001). Birth asphyxia was associated with lower serum insulin, while probable sepsis with relatively higher levels. CONCLUSION: Serum insulin level increases with increasing blood glucose in ill Nigerian babies at presentation to the hospital. Babies with asphyxia and sepsis particularly tend to have abnormal serum insulin at admission. Hyperinsulinaemia in ill babies may connote a compensatory mechanism to normalise abnormal blood glucose rather than playing significant role in its aetio-pathogenesis.